Perfusion Сomputed Tomography in the Diagnosis of Chronic Pancreatitis Complicated by Obstructive Jaundice and in the Differential Diagnosis with Pancreatic Head Adenocarcinoma - T. N. Trofimova; M. Ya. Belikova (Вестник рентгенологии и радиологии)
Objective: to compare the diagnostic effectiveness of computed tomography performed according to the standard protocol and using a perfusion program in the detection of chronic pseudotumoral pancreatitis complicated by obstructive jaundice and in the differential diagnosis with  pancreatic head adenocarcinoma.Material and methods. The investigation enrolled 153 patients with obstructive jaundice treated at the Saint Petersburg Hospital for War Veterans from 2016 to 2020. The cause of jaundice was chronic pancreatitis in 52 (34%) cases and pancreatic head adenocarcinoma in 101 (66%).  Endoscopic ultrasonography-guided histological verification using biopsy and examining the drugs after organ-sparing and radical resection interventions was obtained in all 101 patients (100%) with pancreatic  adenocarcinoma, and in 32 (61.5%) with chronic pancreatitis. A control group consisted of 30 patients with no anamnestic, clinical, or laboratory evidence of pancreatic diseases. All patients underwent abdominal computed  tomography according to the standard protocol and using a perfusion program.Results. The diagnostic effectiveness of the standard computed tomography protocol in the differential diagnosis of chronic pancreatitis and pancreatic adenocarcinoma was: sensitivity 95.5%, specificity 97.3%, and diagnostic accuracy 96.4%; whereas perfusion computed tomography had sensitivity  98.7%, specificity 99.3%, and diagnostic accuracy 98.6%.Conclusion. Perfusion computed tomography is a highly informative method for the differential diagnosis of chronic pancreatitis and pancreatic head adenocarcinoma in patients with obstructive jaundice.